17. VACUUM BLOOD TUBES: DEVELOPMENT AND APPLICATIONS IN MODERN MEDICINE (Vietnam Journal of Community Medicine, 2025)
Objective: To review the development, characteristics, advantages, and challenges of vacuum blood collection tubes in clinical testing compared to traditional methods.Methods: Literature search was conducted on PubMed, from 2010-2024 using keywords: “vacuum blood collection tubes”, “preanalytical errors”, “hemolysis”, “sample quality”… Selection criteria included studies on sample quality, preanalytical factors, and hemolysis reduction solutions.Results: Vacuum blood collection tubes significantly improve sample quality, efficiency, and safety compared to traditional methods. Hemolysis remains a major challenge, especially in emergency departments (rates up to 35%), and pediatric specimens. Using smaller volume tubes (2 mL versus 6 mL) can decrease hemolysis rates from 11.8% to 2.9%. Proper tube selection, correct sampling technique, and staff training are important factors affecting sample quality.Conclusion: Vacuum blood collection tubes provide significant benefits in reducing pre-analytical errors, enhancing safety protocols, and cost-effectiveness. Current research trends focus on developing patient-specific tubes and integration with automated systems.
Keywords: Blood specimen collection; preanalytical phase; hemolysis; sample quality; clinical laboratory techniques